Parental awareness of on-site management of traumatic dental injuries: An online survey - Sarita Gill; Amrita Chawla; Sidhartha Sharma; Vijay Kumar; Nitesh Tewari; Ajay Logani (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2022)
Background: Despite the high prevalence of traumatic dental injuries (TDIs), parents generally lack awareness about dental trauma emergency management. This preliminary study's goal was to assess parents'/guardians' awareness of the treatment of tooth fractures/avulsion. Materials and Methods: A preformed questionnaire in e-format was sent to parents of school-going children. Kolmogorov–Smirnov test and Shapiro–Wilks's test were employed to test the normality of data. In addition, a Chi-square test was performed for quantitative variables. P ≤ 0.05 was considered statistically significant. Results: A response rate of 82.1% was achieved. Approximately 19.6% of parents reported dental injuries, with the majority (51.9%) occurring at home. In avulsion, 54.8% of parents believed that reinserting the tooth back into the socket was possible. For tooth fractures, 36.2% of parents believed that the fractured tooth could be glued. Tap water was preferred as a storage medium (43.3%). An insignificant association was observed with regard to storage media (P > 0.05). Conclusion: Inadequate understanding of the treatment of TDI by the primary caregiver leads to ineffective interventions at the scene of the accident and a poor prognosis for otherwise treatable cases.